Comment on Falade et al. (2016) DNA-barcoding of Clarias gariepinus, Coptedon zillii and Sarotherodon melanotheron from Southwestern Nigeria [version 1; peer review: 1 approved, 1 approved with reservations] - Miller, Jeremy A.; Riemsdijk, Isolde van; Mohd Zacaery, Khalik; Scager, David J.; Schilthuizen, Menno (F1000 Research Ltd., 2019)
A publication by Falade et al. was selected for discussion by a Naturalis Biodiversity Center-Leiden University Journal Club. The study focused on the identification of fish from Southwestern Nigeria using a DNA barcoding approach. Questions raised during the discussion led to a reanalysis and reinterpretation of the data presented. The authors characterize the process of deriving a taxonomic identification from their sequence data as straightforward, but we were concerned that their approach made it nearly impossible to fail to obtain a taxonomic name for each sequence. The value of sophisticated DNA taxonomy, as well as the pitfalls of its naïve application, are discussed. We suggest that journal discussion groups may be an untapped resource for expanding rigorous peer review, particularly for journals that have adopted an open review model.